eQTL set-based association analysis identifies novel susceptibility loci for Barrett esophagus and esophageal adenocarcinoma - Wang, Xiaoyu; Gharahkhani, Puya; Levine, David M.; Fitzgerald, Rebecca C.; Gockel, Ines; Corley, Douglas A.; Risch, Harvey A.; Bernstein, Leslie; Chow, Wong-Ho; Onstad, Lynn; Shaheen, Nicholas J.; Lagergren, Jesper; et al. (Cancer epidemiology, biomarkers & prevention, 2022)
Over 20 susceptibility single-nucleotide polymorphisms (SNP) have been identified for esophageal adenocarcinoma (EAC) and its precursor, Barrett esophagus (BE), explaining a small portion of heritability.Using genetic data from 4,323 BE and 4,116 EAC patients aggregated by international consortia including the Barrett's and Esophageal Adenocarcinoma Consortium (BEACON), we conducted a comprehensive transcriptome-wide association study (TWAS) for BE/EAC, leveraging Genotype Tissue Expression (GTEx) gene-expression data from six tissue types of plausible relevance to EAC etiology: mucosa and muscularis from the esophagus, gastroesophageal (GE) junction, stomach, whole blood, and visceral adipose.